Design and mechanistic characterization of novel antimicrobial and anticancer peptides - Felício, Mário Romão (2020)
The medical field related to bacterial infections and cancer are currently facing currently one of the biggest challenges, mostly due to conventional treatments inefficiency after years of overuse and misuse in clinics. Cases of multi-resistant bacterial infections are increasing every year, according to World Health Organization (WHO), explained by resistant microorganisms’ predominance after antibiotic usage and limited pharmaceutical development of new drugs. As for cancer therapeutics, unspecific treatments that promote severe side effects had another reported consequence, increased cancer resistance, prolonging patients’treatment. As a result, new alternatives are necessary to fight these challenges, such as antimicrobial peptides (AMPs) and anticancer peptides (ACPs). These peptides physical-chemical properties, such as small amino acid sequence, amphipathicity and positive net charge, allow them to act selectively at specific cell membranes, mostly due to electrostatic interactions (cationic vs. anionic membranes). Besides, they can be used against different targets, with reported activity against bacteria, viruses, fungi and cancer cells. In the last case, they are dependent of cancer cell membrane phosphatidylserine (PS) translocation from internal to external membrane leaflet, which increases the negative cell surface charge. Throughout the work here presented, we focused on new AMPs designed according to two different strategies: (i) Pa-MAP 2 and Pa-MAP 1.9, synthetic AMPs redesign from a natural protein from the polar fish Pleuronectes americanus (winter flounder), and (ii) EcAMP1R4, PaDBS1R1 and PaDBS1R6, synthetic peptides designed through a bioinformatics algorithm that considers chemical properties and activity efficiency. In both cases, a multidisciplinary approach was performed, using biophysics and cell biology techniques to study their activity in vitro, using membrane models, bacterial and cancer cell lines, and in vivo infection models. Considering the Pa-MAP peptide family (Pa-MAP 2 and Pa-MAP 1.9), with a minimal inhibitory concentration (MIC) of 3.2 and 6.0 μM against Escherichia coli, respectively, they were shown to be efficient against a multi-resistant strain from a clinical isolates, inclusively with promising results demonstrated with an in vivo infection mice model. Nevertheless, only Pa-MAP 1.9 showed to have dual activity (AMP and ACP), being tested in two different cell lines, HeLa and HCT-166. Despite its efficiency in promoting cancer cell death, Pa-MAP 1.9 showed a different mechanistic behaviour for the cell lines tested, promoting total cell death after 6 h of incubation (IC50 of 51.8 ± 1.23 μM) and membrane homeostasis destabilization. As for the synthetic peptides (EcAMP1R4, PaDBS1R1 and PaDBS1R6), their antimicrobial activity was confirmed in vitro, according to bioinformatics studies, with MIC values against E. coli of 11.7, 1.5 and 8.0 μM, respectively. In vivo studies were also performed for the last two peptides, confirming their potential as future antimicrobial drug molecules. Their dynamics after membrane interaction was likewise studied, either using bacteria cells or lipid vesicles, showing that different biomembrane properties are destabilized, which could determinate AMP efficiency. Structure conversion to a-helix after membrane interaction showed to be the first step for peptide activity. Concluding, the work discussed in this thesis resulted in new peptide molecules that are effective AMPs and, one of them (Pa-MAP 1.9), also as ACP. Their activity was characterized in vitro and in vivo through new approaches, with the objective of identifying new insights that may help in future peptide design. Even with the promising results achieved so far, their potential use in therapeutics need to be further tested, considering their efficiency, but also their applicability, focusing on patients and in the pharmaceutical industry needs.